Starch metabolism in green algae - Busi, María Victoria (2014)
Starch plays a central role in the life cycle as one of the principal sources of chemical energy. This polysaccharide accumulates in plastids in green algae and land plants, and both organisms have acquired various enzyme isoforms for each step of the metabolic pathway. Eukaryotic green microalgae present the critical photosynthetic functions as higher plants. However, due to the small size of their genome, gene redundancy is decreased, a feature that makes them an excellent model for investigating the properties of photosynthetic physiology. In the last decade, there has been an increasing demand for starch in many industrial processes, such as food, pharmaceutical, and bioethanol production. Thus, a better understanding of starch biosynthesis, in particular the structure-function relationship and regulatory properties of the enzymes involved in its production may provide a powerful tool for the planning of new strategies to increase plant biomass, as well as to improve the quality and quantity of this polymer.